2015
DOI: 10.1007/s40993-015-0002-x
|View full text |Cite
|
Sign up to set email alerts
|

The Mordell integral, quantum modular forms, and mock Jacobi forms

Abstract: It is explained how the Mordell integral R e πiτ x 2 −2πzx cosh(π x) dx unifies the mock theta functions, partial (or false) theta functions, and some of Zagier's quantum modular forms. As an application, we exploit the connections between q-hypergeometric series and mock and partial theta functions to obtain finite evaluations of the Mordell integral for rational choices of τ and z. Mathematics Subject Classification: 11P55, 05A17Keywords: Jacobi forms; mock Jacobi Form; partial Jacobi theta function; False t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In the particular case of λ ∈ N/2, we derived an all-order formula for the perturbative contributions, that becomes particularly handful in the limit of infinite β. We have also shown that the exact expression for our bi-local correlators is closely related to the Mordell integral, a basic constituent in the theory of Mock-modular forms [31].…”
Section: Jhep05(2021)140 7 Final Comments and Outlookmentioning
confidence: 68%
See 1 more Smart Citation
“…In the particular case of λ ∈ N/2, we derived an all-order formula for the perturbative contributions, that becomes particularly handful in the limit of infinite β. We have also shown that the exact expression for our bi-local correlators is closely related to the Mordell integral, a basic constituent in the theory of Mock-modular forms [31].…”
Section: Jhep05(2021)140 7 Final Comments and Outlookmentioning
confidence: 68%
“…Moreover, the alternate sign of the perturbative orders points towards a possible Borel summability for the full series. As a final observation, we point out that the exact expression for the bi-local correlator can also be written in terms of Mordell integrals [29], suggesting a link with the world of Mock-modular forms [30,31]. The paper's structure is the following: in section 2, we review the exact results [17,19] and discuss the perturbative computation of the bi-local correlator in JT gravity from the Schwarzian perspective.…”
Section: Jhep05(2021)140mentioning
confidence: 99%
“…Mordell showed that the above integral can be reduced to two standard forms, namely, ϕ(z, τ ) := τ Kuznetsov [28] has recently used h(z; τ ) to simplify Hiary's algorithm [22] for computing the truncated theta function n k=0 exp(2πi(zk+τ k 2 )), which in turn is used to compute ζ 1 2 + it to within ±t −λ in O λ (t 1 3 (ln t) κ ) arithmetic operations [21]. We refer the reader to a more recent article [9] and the references therein for further applications of Mordell integrals.…”
Section: Introductionmentioning
confidence: 99%
“…Kuznetsov [28] has recently used h(z; τ ) to simplify Hiary's algorithm [22] for computing the truncated theta function n k=0 exp(2πi(zk+τ k 2 )), which in turn is used to compute ζ 1 2 + it to within ±t −λ in O λ (t 1 3 (ln t) κ ) arithmetic operations [21]. We refer the reader to a more recent article [9] and the references therein for further applications of Mordell integrals.…”
Section: Introductionmentioning
confidence: 99%